2019
DOI: 10.1371/journal.pone.0220621
|View full text |Cite
|
Sign up to set email alerts
|

Small-RNA analysis of pre-basic mother plants and conserved accessions of plant genetic resources for the presence of viruses

Abstract: Pathogen-free stocks of vegetatively propagated plants are crucial in certified plant production. They require regular monitoring of the plant germplasm for pathogens, especially of the stocks maintained in the field. Here we tested pre-basic mother plants of Fragaria , Rubus and Ribes spp., and conserved accessions of the plant genetic resources of Rubus spp. maintained at research stations in Finland, for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the last years, performing RNA-sequencing analysis for determination and discovery of plant viruses in crop plants has become widespread ( Rott et al, 2017 ; Zheng et al, 2017 ; Maliogka et al, 2018 ; Massart et al, 2019 ; Rajamäki et al, 2019 ; Mehetre et al, 2021 ). More specifically, Al Rwahnih et al (2009) pioneered the use of HTS for virus determination in grapevine; and since then, it has proved a valuable tool ( Coetzee et al, 2010 ; Pantaleo et al, 2010 ; Al Rwahnih et al, 2015 ; Maree et al, 2015 ; Jo et al, 2015 ; Czotter et al, 2018 ; Hily et al, 2018 ; Vigne et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, performing RNA-sequencing analysis for determination and discovery of plant viruses in crop plants has become widespread ( Rott et al, 2017 ; Zheng et al, 2017 ; Maliogka et al, 2018 ; Massart et al, 2019 ; Rajamäki et al, 2019 ; Mehetre et al, 2021 ). More specifically, Al Rwahnih et al (2009) pioneered the use of HTS for virus determination in grapevine; and since then, it has proved a valuable tool ( Coetzee et al, 2010 ; Pantaleo et al, 2010 ; Al Rwahnih et al, 2015 ; Maree et al, 2015 ; Jo et al, 2015 ; Czotter et al, 2018 ; Hily et al, 2018 ; Vigne et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another genome (RYNV-BS, KM078034, Diaz-Lara et al, 2015) was sequenced from red raspberry 'Baumforth's Seedling A' using DNA from rolling circle amplification. Since then, several RYNV sequences were published using small RNA (Rajamäki et al, 2019) or whole genome sequencing (MN245240). Diaz-Lara (2016) observed that red raspberry plants, supposedly free of RYNV based on aphid or graft transmission onto R. occidentalis 'Munger' indicator, yielded positive results when indexed by PCRbased assays.…”
Section: Introductionmentioning
confidence: 99%
“…Blackcurrant reversion virus (BRV), transmitted by the gall mite ( Cecidophyopsis ribis ), is the most significant virus in blackcurrants, causing disease symptoms to the leaves and flowers, proliferation, and ultimately yield losses [ 33 , 34 ]. Pest and disease infections can be prevented in certified plant production by maintaining pre-basic mother plants (stock material) in insect-proof greenhouse [ 35 ].…”
Section: Introductionmentioning
confidence: 99%